The compositionally distinct cyanobacterial biocrusts from brazilian savanna and their environmental drivers of community diversity - Machado de Lima, Náthali Maria (2019)
Fil: Machado de Lima, Náthali Maria. São Paulo State University (UNESP). Microbiology Graduation Program. Department of Zoology and Botany. São Paulo, Brazil.